2003
DOI: 10.1038/sj.npp.1300338
|View full text |Cite
|
Sign up to set email alerts
|

Central Opioid Receptors Differentially Regulate the Nalmefene-Induced Suppression of Ethanol- and Saccharin-Reinforced Behaviors in Alcohol-Preferring (P) Rats

Abstract: The exact opioid-sensitive receptors participating in EtOH-seeking behaviors remains unclear. Previous studies have reported higher densities of m-opioid receptor binding in the nucleus accumbens (NACC) of P relative to NP rats; however, no differences were seen in d-receptor binding. In contrast to the NACC, substantially lower levels of m-receptor binding have been observed in the ventral tegmental area (VTA) of both P and NP rats, albeit no line differences have been observed. In the present study, opioid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 49 publications
(92 reference statements)
4
38
1
Order By: Relevance
“…Nor-BNI selectively attenuated ethanol self-administration in dependent animals (**po0.01, ***po0.001 compared to vapor-exposed vehicle dose). published literature which identifies that both nalmefene (June et al, 1998(June et al, , 2004 and naltrexone (Stromberg et al, 1998(Stromberg et al, , 2001Coonfield et al, 2002;Shoemaker et al, 2002;Stromberg, 2004) have the ability to attenuate ethanol consummatory behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Nor-BNI selectively attenuated ethanol self-administration in dependent animals (**po0.01, ***po0.001 compared to vapor-exposed vehicle dose). published literature which identifies that both nalmefene (June et al, 1998(June et al, , 2004 and naltrexone (Stromberg et al, 1998(Stromberg et al, , 2001Coonfield et al, 2002;Shoemaker et al, 2002;Stromberg, 2004) have the ability to attenuate ethanol consummatory behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…As well, local administration of an opioid antagonist into the nucleus accumbens (NAC) decreased alcohol consumption and operant responding for alcohol in both nonselected and selectively bred alcohol-preferring rats (Heyser et al 1999;Hyytiä and Kiianmaa 2001;June et al 2004). In addition, microdialysis studies have shown that acute alcohol treatment increased the extracellular concentration of β-endorphin in the NAC of nonselected lines of rats (Marinelli et al 2003;Olive et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nalmefene is a more potent antagonist at d-opioid receptors (DeHaven-Hudkins et al, 1990;Emmerson et al, 1994) that have been implicated in alcohol drinking (Ciccocioppo et al, 2002;June et al, 2004), and the plasma terminal half-life of oral nalmefene (Dixon et al, 1987;Gal et al, 1986) markedly exceeds that of naltrexone (Meyer et al, 1984). Single oral nalmefene doses of 20-300 mg and repeated doses of 10-40 mg twice a day have been well tolerated (Dixon et al, 1987;Mason et al, 1994), and there have been no reports of any serious adverse drug reactions on hepatic or other body systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nalmefene reduces alcohol drinking in preclinical models (June et al, 1998;June et al, 2004). Recent findings indicate that nalmefene and naltrexone are equally effective in reducing subjective responses to alcohol in alcoholics (Drobes et al, 2004), and in clinical studies, nalmefene has been associated with significant decreases vs placebo in reducing relapse to heavy drinking (Mason et al, 1994;Mason et al, 1999).…”
Section: Introductionmentioning
confidence: 99%